Assessment of nutritional value, aerobic stability and measurement of in vitro fermentation parameters of silage prepared from several leguminous plants - ShiJia Yang; Kai Zhang; RuiXuan Ji; XueWen Chen; Jiao Wang; Imtiaz Hussain Raja; AnShanShan; SuJiang Zhang (BMC Plant Biology)
Abstract The livestock sector plays a pivotal role in rural socio-economic development, particularly in arid regions. Making silage is one method for storing feed during the dry season, while leguminous species serve as indispensable resources in livestock production systems due to their nutritional and ecological benefits. This study aimed to select suitable forage resources by evaluating several available leguminous species ( Arachis hypogaea (peanut vines), Sophora alopecuroides, Glycyrrhiza glabra (liquorice), and Medicago sativa (Alfalfa)) in Alar, Xinjiang, China, and comprehensive analyses of fermentation quality, aerobic stability, and in vitro rumen fermentation were conducted to assess their nutritional value and relieve arid regions feed shortages. The fermentation analysis indicated that Sophora alopecuroides exhibited the optimal quality, showing significantly higher lactic acid and lower ammonia nitrogen (NH3-N) concentrations than the other species (P < 0.05). Following a 12-day aerobic exposure, all the legume silages exhibited increased dry matter (DM), pH, and NH3-N concentrations alongside a decreased water-soluble carbohydrates (WSC) content. Alfalfa and Sophora alopecuroides silages maintained significantly higher lactic acid bacteria populations than other varieties (P < 0.05). In vitro rumen fermentation revealed alfalfa silage achieved peak biogas production at 72 h, while liquorice silage showed significantly lower NH3-N content than other groups (P < 0.05). Alfalfa and Sophora alopecuroides silages demonstrated superior gas production and DM degradation rates, indicating their enhanced fermentative characteristics. In summary, alfalfa and sophora alopecuroides could be of the suitable plants for making high-quality silage. However, additional research is needed to study the effect of the silages on animal growth performance.